Respuesta :

Answer:

The answer is C

Step-by-step explanation:

Use the method of elimination

First rearrange the first equation to look like the second

[tex]2x + 3y = 17 \\ 4x + 6y = 34 \\ - 4x - 6y = - 34[/tex]

Next add the two equations together eliminating the y term.

[tex] - 4x - 6y = - 34 \\ 3x + 6y = 30 \\ \\ - x = - 4 \\ x = 4[/tex]

There's only one answer with x = 4 so you're done. To go further, substitute x = 4 into the second equation and solve for y

[tex]3x + 6y = 30 \\ 3 \times 4 + 6y = 30 \\ 12 + 6y = 30 \\ 6y = 18 \\ y = 3[/tex]

Answer:

c

Step-by-step explanation: